PERBANDINGAN JENIS SEMEN PCC DAN OPC DENGAN UJI KONSISTENSI NORMAL DAN WAKTU IKAT SEMEN - Adhi, Bagas Wahyu; Hariyani, Betty; Nurrohim, Rio Ridwan; Nugroho, Satrio Adi Wahyu; Safarizki, Hendramawat Aski; Qomaruddin, Mochammad (Universitas PGRI Semarang, 2026)
Cement setting time is the time required for cement to harden, calculated from when the cement begins to react with water to form a paste. Cement setting time refers to the period of time required for cement paste mixed with water to become stiff enough to form a structure and bind construction materials. The purpose of this study was to determine the normal consistency of cement and cement setting time for PCC and OPC cement. The results of this study are for the Normal Consistency test of Portland Cement PCC Ex. Tiga Roda with a penetration target of 10 mm obtained a water content of 30.8%. Normal Consistency test of Portland Cement OPC Ex. Tiga Roda with a penetration target of 10 mm obtained a water content of 26.4%. Testing the Setting Time of Portland cement PCC Ex. Tiga Roda obtained penetration at Initial Setting of 112 mm, Final Setting of 210 mm. Testing the Setting Time of Portland cement OPC Ex. Tiga Roda obtained penetration at Initial Setting of 111 mm, Final Setting of 210 mm.